FINANCIAL FORECASTS FOR WORKS CONTRACTS. A CONTENT ANALYSIS OF ROMANIAN RULES ON VALUE ADJUSTMENTS - Cristian DOGAR (Annals of the University of Oradea: Economic Science)
Unpredictable events, such as: international market prices evolution of construction materials, fuel and energy, changing rules regarding labour, wages and mobility of goods may lead to cost escalation during works contracts implementation. A proper value adjustment formula may contribute on managing emerging financial risk. Generally, those formulas are subject to national rules, but only for public investments, of great value and long duration, the rest remaining to the contracting authorities’ decisions. Looking for the right formula in those cases of non-regulated situations induces stress for personnel, and also the risk of affecting investments performance through wrong decision. The paper’s objectives are both qualitative and quantitative, searching, through a relevant Romanian legal frame content analysis for answers at two research questions: how a works contract value could be adjusted, and how can be choose the most appropriate one among different value adjustment formulas? A selection of contemporary relevant national rules and regulations on value adjustment formulas was studied to answer at these questions, revealing specific approaches on treating adjustments. Results of this content analysis refers to the presenting and discussing various models of value adjustment approach in Romanian works contracts. Paper’s conclusions could be used by researchers in further investigation of relationship between various value adjustment formulas and investment's performance. Conclusions could be also useful for practitioners, in selecting the appropriate value adjustment formula in case of non-regulated such as relatively small value and short duration works contracts. As a personal contribution, a model on selecting a value adjustment formula is here presented.